Cloud Security Adoption Factors in Educational Institutions - Olivia E.S Liando; Marshel R. Kapahang; John Reimon Batmetan Batmetan (JR Education, 2022)
In recent years, cloud computing technology has emerged as one of the technologies that are currently hot or often used both in the world of work, online shopping (E-Commerce), and the world of education. Before we use any technology, we must first understand the security system that exists in that technology, including the security system in Cloud Computing Technology. In the world of education today, many schools and universities have implemented Cloud Computing Technology in learning systems and database storage. Currently, Cloud Computing provides 3 different services such as Saas, PaaS, and IaaS which can be used by organizations as private, public, and, Hybrid. Security is the main concern so that there is no data theft in the world of Education. This journal was created using the Literature Study by searching from several selected journals that already exist as knowledge, in order to better understand the Cloud Computing security system.